Implementation of Digital Tools in Classroom Management: a Study of Student’s Engagement in Merauke Musamus University - Najdah Thalib; Prima Lestari Situmorang; Juli Arianti; Mutiya Oktariani; Damayanti Damayanti (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The implementation of digital technology in management is expected to bring positive impacts on learning. This research aims to investigate the use of digital tools in classroom management and its effect on student engagement at Merauke Musamus University. A mixed-method quantitative-qualitative approach is employed, with a quasi-experimental research design that involves test, survey, and interview. This research involved 100 students from the Faculty of Economics and Business: Class A and Class C from the Management department and Class C from the Accounting department. The data were collected thought pre-test & post-test, and questionnaires. The result of the test reveals the average score of experimental groups are higher 84.20 compared to the control groups’ 77.40, t-value (5.665) is greater than the critical t-value (1.660) at a significance level of 5%. The data from the observation and interview show the students positive attitudes towards the implementation of digital tools in learning. The findings indicate that the implementation of digital tools in classroom management positively impacted student engagement in both the experimental and control groups. However, the experimental group, which received the intervention of digital tools, demonstrated higher engagement compared to the control group, which did not receive the intervention